3D.02: BLOOD PRESSURE VARIABILITY INCREASES WITH ADVANCING CHRONIC KIDNEY DISEASE STAGE. A CROSS-SECTIONAL ANALYSIS OF 14, 382 HYPERTENSIVE PATIENTS FROM SPAIN. (June 2015) - Gorostidi, M.; Sarafidis, P.; Sierra, A. De La; Banegas, J.R.; De La Cruz, J.J.; Vinyoles, E.; Segura, J.; Ruilope, L.M.
Abstract : Objective: Increased blood pressure (BP) variability has been related to cardiovascular morbidity and mortality in hypertensive patients. We aimed to assess short-term BP variability by means of ambulatory BP monitoring (ABPM) according to renal function status. Design and method: We conducted a cross-sectional analyses with data from 14 382 hypertensives included in the Spanish ABPM Registry. Performance of ABPM was standardized according to guideline recommendations. Kidney function was graded according to current KDIGO definitions for chronic kidney disease (CKD) staging. Estimated glomerular filtration rate was calculated by the CKD-EPI equation. Short-term (reading-to-reading) BP variability was assessed by standard deviation (SD) of mean daytime and nighttime systolic BP (SBP) and diastolic BP (DBP). Results: Mean age of the population was 61.0 ± 13.9 years and 52.6% of patients were male. Distribution according to renal function status was: 8, 689 (60.4%) with no CKD, 765 (5.3%) with stage 1 CKD, 494 (3.4%) with stage 2 CKD, 3893 (27.1%) with stage 3 CKD, 413 (2.9%) with stage 4 CKD, and 128 (0.9%) with stage 5 CKD. SD of daytime SBP was higher at more advanced CKD stage (13.6 in CKD-free patients, and 15.7, 16.7, 15.7, 17.5, and 19.0 mmHg in stage 1 to 5 CKD patients respectively, p-trend < 0.001). SD of nighttime SBP also increased with progressive CKD stage, with the change being proportionally higher than that observed for daytime SBP (15.1 in CKD-free patients, and 17.5, 18.8, 17.7, 20.1, and 23.8 mmHg in stage 1 to 5 CKD patients respectively, p-trend < 0.001). SD of daytime DBP and nighttime DBP also increased as renal function worsened but with only marginal statistical significance. Conclusions: Increased short-term BP was significantly associated with progressive CKD stages in a large sample of hypertensive patients. This association was stronger for SBP than for DBP, and for nighttime than for daytime BP. We suggest that increased SBP variability, particularly at night, may partially explain the sharp elevation of cardiovascular risk with worsening renal function.